The crust structure of the Morasko meteorite – a preliminary hypothesis - Stankowski, Wojciech T.J. (Geologos, 2017)
A small piece of the Morasko meteorite, weighing 970 g, yields traces of its journey through the Earth’s atmosphere and of its impact into a mineral substrate, such as reflected in the meteorite’s crust. This is seen in the crust structure in the form of sintered as well as fusion and semi-fusion layers for which ablative niches are optimum sites. Subsequent weathering processes have resulted in significant mineralogical changes in the crusts. The meteorite crusts originated during polygenetic processes.